INVESTIGATION AND ANALYSIS OF LOW LOSS OPTICAL FIBER COUPLER - YEOH, KENG SING (IRC, 2019)
The main objective of this project was to develop the fiber optic transmission coupler, mainly focus on passive optical fiber coupler. Fiber coupling with losses remains a vital part of optical fiber network. An ideal fiber couplers should transfer light with no loss and should have complete insensitivity to the dispersion of light among the fiber cable and the state of polarization of light. In reality, the performance of optical fiber system usually determines by the characteristics of the device. In this project, the losses associated with coupling light from one cable into another was investigated, how coupling losses are affected by end gap distance, and by the amount of angular and lateral misalignment between fiber ends were deduced and the acceptance angle for the light to pass through the optic fiber cable was studied. Further analysis on the coupling structure and attenuation analysis were performed on the transmission line using test, measurement and simulation tools like OTDR. OTDR is an instrument for fiber optic testing which used to measure, locate, identify and detect optical events at any point of the fiber optic link. The recommendation for this project is to carry out more studies for fiber optical communication for a better understanding of the theory, acquire newer and upgraded version of the fiber optic transmitter/receiver module to improve the results, and simulate the test result with simulation software.